TRANSLATION SHIFTS IN THE INDONESIAN SUBTITLE OF GUY RITCHIE’S THE COVENANT (2023) MOVIE - Ahmad, Lusiana; Warsidi, Warsidi; Halim, Nur Muthmainnaah (UC Journal: ELT, Linguistics and Literature Journal, 2024)
Translation is important for people who don't know a foreign language. Translators face challenges, but use of techniques like translation shifts can make translations sound more natural and effectively communicate the original meaning to the target audience. This research aims to identify the types of translation shifts used in the Indonesian subtitle of Guy Ritchie’s The Covenant movie and to identify the possible reasons the translators used translation shifts in this movie. The research applied the theory of translation shift proposed by Catford to analyze the data. It used descriptive qualitative methods and the data is from the movie subtitle of Guy Ritchie’s The Covenant. The researcher used the Oxford Dictionary and Big Indonesian Dictionary (KBBI) applications as instruments for analyzing the data, and to ensure the analysis results. The analysis found that the Indonesian subtitles for Guy Ritchie’s The Covenant movie included all types of shifts as proposed by Catford's theory. The shifts identified in the Indonesian subtitles included level shifts and category shifts (including structure shift, unit shift, class shift, and intra-system shift). However, among these shifts, category shifts especially unit shifts, were the most dominant. The translator probably used these translation shifts due to cultural and linguistic differences, time constraints, and creative translation choices.